The Role of Jordanian Universities in Encountering Students’ Intellectual Extremism - Bataineh, Omar Taiseer; Jaradat, Mahmoud Khalid; Alzoubi, Zuheir Hussein (Dirasat: Educational Sciences, 2020)
The study aims at recognizing the role Jordanian universities in encountering the aspects of students’ intellectual extremism and determining if there are statistically significant differences in that role due to sex, college, academic year, grade point average, and type of admission. The researchers used a survey, where a stratified and random sample that consisted of (928) students representing (1.5%) of the students of Hashemite University and Yarmouk University was chosen. The findings of the study showed that the degree of the role played by Jordanian universities in encountering intellectual extremism was high. In addition, the results revealed statistically significant differences in the degree of that role due to sex, college, academic year, grade point average, and type of admission. Finally, the researchers recommended enhancing the role of Jordanian universities in encountering students’ intellectual extremism and educating students about intellectual deviations.